Retrospective observational study on the epidemiological profile of people living with HIV/AIDS in Pernambuco state, Brazil - Maria Rosângela Cunha Duarte Coêlho; Thaísa Regina Rocha Lopes; Juliana Prado Gonçales; Luan Araujo Bezerra; Mirela Lopes Ribeiro; Georgea Gertrudes Mendes de Oliveira Cahú; José Valter Joaquim Silva Júnior (Journal of Infection in Developing Countries)
Introduction: HIV/AIDS is a major global public health concern. In Pernambuco state, Brazil, the number of people living with HIV/AIDS (PLWHA) is among the highest in the country. Herein, a cross-sectional retrospective observational study was carried out with 811 PLWHA followed up at the Clinical Hospital, Pernambuco, Brazil, between 2013 and 2017.